11C-carbonylation reactions using gas–liquid segmented microfluidics. Issue 108 (20th October 2015) - Dahl, Kenneth; Schou, Magnus; Ulin, Johan; Sjöberg, Carl-Olof; Farde, Lars; Halldin, Christer
Abstract : A novel gas–liquid segmented microfluidic platform has been developed, allowing for the direct access to 11 C-labelled drug-like molecules. Abstract : A novel gas–liquid segmented microfluidic platform has been developed. The Pd-mediated 11 C-carbonylation reaction proceeds smoothly on this platform and good to excellent radiochemical conversions (RCC) were observed. Twelve compounds were successfully radiolabelled using this novel technology, including the well established D2 receptor radioligands [ 11 C]raclopride and [ 11 C]FLB 457.